2014
DOI: 10.1371/journal.pone.0109425
|View full text |Cite
|
Sign up to set email alerts
|

A Rare HBV Subgenotype D4 with Unique Genomic Signatures Identified in North-Eastern India –An Emerging Clinical Challenge?

Abstract: Background/AimsHBV has been classified into ten genotypes (A–J) and multiple subgenotypes, some of which strongly influence disease outcome and their distribution also correlate with human migration. HBV infection is highly prevalent in India and its diverse population provides an excellent opportunity to study the distinctiveness of HBV, its evolution and disease biology in variegated ethnic groups. The North-East India, having international frontiers on three sides, is one of the most ethnically and linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Phylogenetic analyses showed that the Brazilian HBV/D4 formed a distinct clade, with few sequences from East Africa, Cape Verde and from the region of Tripura, India. As Brazil, India also faced successive waves of colonization, and multiple episodes of human migration [48]. It is possible that, due to the geographical proximity of Tripura with the Portuguese colony of Hughli in India, HBV/D4 isolates would have been introduced in Brazil from Asia or East Africa by the Transatlantic trade, as stated for the Asian-American clade of subgenotype A1.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses showed that the Brazilian HBV/D4 formed a distinct clade, with few sequences from East Africa, Cape Verde and from the region of Tripura, India. As Brazil, India also faced successive waves of colonization, and multiple episodes of human migration [48]. It is possible that, due to the geographical proximity of Tripura with the Portuguese colony of Hughli in India, HBV/D4 isolates would have been introduced in Brazil from Asia or East Africa by the Transatlantic trade, as stated for the Asian-American clade of subgenotype A1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis did not establish when D7 diverged from D5 and where it occurred. Interestingly, a recent study reported that D7 formed a significant phylogenetic group with D4, a rare subgenotype that has been found in African countries such as Rwanda, Kenya, Ghana, and Morocco [Banerjee et al, ]. On this basis, an hypothesis that should be explored using a wider sequence dataset, speculates that a common ancestor of D4 and D7 diverged from D5 in India, reached Africa and Maghreb area where D4 and D7 diverged.…”
Section: Discussionmentioning
confidence: 99%
“…Of the ten D-subgenotypes so far identified, D1–D7 and D10 are non-recombinant types while D8 and D9 are D/E and D/C recombinants respectively 3 , 5 . Six out of the ten D-subgenotypes, namely D1–D5 and D9 had been reported from different parts of India 3 , 13 , 14 . In the present study, we performed a comprehensive analysis of the virological features and cytopathic effects of four non-recombinant D-subgenotypes, D1, D2, D3 and D5, prevalent in Eastern India to gain an insight into their potential contribution to disease progression, which in turn will help in the design of appropriate surveillance and therapeutic strategies for the management of HBV/D-infected patients.…”
Section: Introductionmentioning
confidence: 99%